The dynamics of God"s reign as a hermeneutic key to Jesus" eschatological expectation - Urbaniak, Jakub (HTS teologiese studies, 2016)
With this study, we seek to contribute to the theological discussion regarding the nature and the meaning of the Christian eschaton. We will argue that the dynamics of God’s reign provide a hermeneutic key to Jesus’ ‘eschatological expectation’. It is not possible to grasp the full meaning of Jesus’ urgent expectation of the end unless one realises that God’s action is always eschatological. That is to say, right from creation, God is always acting in history in an eschatological way, though only in Jesus does this action reach its ultimate goal. By critically examining the multifaceted views of selected contemporary theologians, we will suggest that Jesus’ eschatological expectation may be adequately interpreted only in light of God’s ‘eschatological reign’. In this context, the tension between the already present and not yet fully realised dimensions of God’s reign appears as a promising hermeneutic key to Jesus’ teaching in general and his eschatological expectation in particular. The article consists of two sections. Firstly, we will give a brief account of the dynamics of God’s reign, interpreted according to the ‘middle way’ between consistent and realised eschatology. In the second part, our focus will be on the eschatological expectation: its development in the Jewish tradition; on how Jesus applied, or rather re-appropriated, it in his mission; and whether or not his emphasis on the imminence of an eschaton was a result of him being mistaken.